Did you hear about Kitty Karr? - Smith Paul, Crystal (New York : Henry Holt and Company, 2023)
"When white silver screen icon Kitty Karr Tate dies and bequeaths her multimillion-dollar estate to the three Black St. John sisters, it prompts questions. A celebrity in her own right, Elise St. John would rather focus on sorting out Kitty's affairs than deal with the press. But what she discovers in one of Kitty's journals rocks her world harder than any other brewing scandal could-and between a cheating fiancé and fallout from a controversial social media post, there are plenty. The truth behind Kitty's ascent to stardom from her beginnings in the Jim Crow South threatens to expose a web of unexpected family ties, debts owed, and debatable crimes that could, with one pull, unravel the all-American fabric of the St. John sisters and those closest to them"--.
"Reese's Book Club."--Cover jacket.
new book 2024 winter.
Keywords: African Americans -- Fiction; African American women -- Fiction; FICTION / Alternative History; Feminine; Novels